Plasmas Afterglows in N_2-O_2 Discharges - Ricard , A.; Pointu , A. M.; Oh , S. G. (Plasmas Afterglows with \(N_2\) for Surface Treatments- Edition 2, 2022)
The \(N\) and O-atoms density versus the \(O_{2}\) percent from 1 to \(4 %\) into \(N_{2}\) in \(HF\) flowing afterglow (at 7 Torr \(, 0.5 slpm, 150 ~W\) ) was strongly decreasing for \(N\) atoms from 15 to \(210^{14} ~cm^{-3}\) and kept a nearly constant value for \(O\)-atoms density : 7-9 10 \(14 ~cm^{-3}\), a value which is higher than the N-atom density in the range \(2-10 % O_{2}\) into \(N_{2}\). In RF afterglows, it was studied the effect of O-atoms and \(O_{2}\) molecules when \(O_{2}\) was introduced into \(N_{2}\) before or after the plasma ( 8 Torr, \)1 slpm, 100 ~W\) ). It is concluded to a quenching of \(N_{2}\) active species by O-atoms more effective than with \(O_{2}\) in the early and late afterglows. At \(N_{2}\) atmospheric gas pressure of DBD and Corona plasmas with \(O_{2}\) impurity, it has been measured a density of the \(N_{2} O_{s}^{1}\) excimer equal to about $10^{12} ~cm^{-3}\), largely less than the \(N\) and \(N_{2}(~A)\) densities : (5-7) \(10^{14} ~cm^{-3}\).